Direct and enhanced delivery of nanoliposomes of anti schizophrenic agent to the brain through nasal route - Pratik Upadhyay; Jatin Trivedi; Kilambi Pundarikakshudu; Navin Sheth (Elsevier, 2017)
The problem of inadequate oral bioavailability of Quetiapine Fumarate, a lipophilic drug used for schizophrenia, due to hepatic metabolism and repulsion by brain barrier was attempted in this study. Combination of two approaches, viz. Quetiapine inclusion into the liposomal carrier for better diffusion and administration through nasal route to avoid hepatic metabolism and barrier elimination was applied. Thin film hydration followed by sonication method was employed in liposome preparation and the formulation was optimized using 32 full factorial design. The number of sonication cycles (X1) of 2 min and 80% amplitude and molar ratio of constructional components such as cholesterol to egg phosphatidylcholine (X2) as independent variables and a % of entrapment efficiency (Y1) and cumulative in vitro drug release (Y2) at 6 h as dependent variables was selected. Batch F7 prepared by 2 cycles of sonication and 1:3 M ratio of cholesterol:egg phosphatidylcholine was optimized as a consequence of substantial entrapment efficiency of 75.63 ± 3.77%, and 99.92 ± 1.88% drug release and 32.33 ± 1.53% drug diffusion, which was optimum among all other batches at 6 h. Diffusion study was done for all the batches of liposomal formulation by using sheep nasal mucosa and good amount with better diffusion rate was measured which proved liposomal dispersion a virtuous delivery system for brain drug delivery through nasal route. Results of in vivo, ciliotoxicity and gamma scintigraphy studies on mice supported the above inference.